A Comparative Study on Preferences in Selection of Dishes by Guest in Pre and Post Covid -19 at 5-Star Hotels in Delhi NCR (Global Journal of Management and Business Research, 2022)
In just few weeks COVID-19 immerses in the world, affecting intimidating the lives and health of millions of people all around the world. The Pandemic also extremely impacted the Hospitality and Tourism industry across the country. Its effect disrupted human lives and pushed the country to an economic slowdown. This Pandemic brought fear of travel and dining out, on every person be it a domestic or an international traveller. Lockdowns and intra state travel ban, and the fear of being quarantined took its toll on Hospitality and Tourism Industry. In This paper researchers
Keywords: covid-19; hospitality industry; hygiene; healthcare; pandemic